Educational Culture Of Reward And Punishment In Delivering Education At Modern Dayah Of Aceh Besar District - Jamaluddin Thaib (International Journal of Education, Vocational and Social Science, 2023)
The application of reward and punishment is also in line with the concepts of the Qur'an and hadith, even education experts support these two approaches with the note that punishment is the last alternative, and its application must be based on compassion, fairness, not hurting and having educational value. But in reality, there are still many imbalances in its application, especially in the integrated dayah at Aceh Besar District. The purpose of this study was to find out the elements of educational culture in integrated Islamic boarding schools, to find out the forms of reward and punishment in organizing education and knowing the impact of implementing the reward and system system punishment for the behavior of students. In order for this research to be more accurate, the researchers used a qualitative method with a phenomenological approach. Through this method, researchers try to comprehensively examine the symptoms that occur in the field according to the focus of the problem. Based on the results of research conducted by the authors indicate that. First, the cultural elements of integrated dayah education have been well formed, starting with the inculcation of elements of faith and spiritual rituals, educational activities that take place according to schedule, learning climate and discipline, rules and curriculum, interaction and communication media, teachers and leaders who become exemplary figures and the existence of artifacts/symbols as a work of art. Second, in the application of reward and punishment it was found that punishment is still prioritized compared to reward, there is still no standardization and there is also no complete evaluation of reward and punishment. punishment imposed. Third, the existence of various imbalances in the application of punishment has an impact on the behavior of some students who are unhappy, depressed, traumatic and want revenge on other students.